PKM Bimbingan Teknis Memandikan Mayat di Era New Normal pada Mahasiswa FIK UNM - Muhammadong Muhammadong; Nurmila Nurmila (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Bathing a corpse is not a small matter that must be viewed unilaterally so that not many people are interested in the job but this profession is an obligation that must be fulfilled for the living. In terms of regulations, bathing a corpse has rules that must be fulfilled so that its implementation can be in accordance with Islamic teachings. The involvement of FIK UNM students in technical guidance in bathing the body so that students can gain knowledge about the procedures for bathing the body so that it can be implemented in the community.